Disposition to trust, interpersonal trust and institutional trust of mobile banking in Malaysia - Mahad, Murat; Mohtar, Shahimi; Othman, Abdul Aziz (Asian Fellowship of Academic Professional, 2015)
Mobile banking refers to the use of smart phones or other mobile devices to perform tasks online banking from your home computer, such as monitoring the account balances, transfer of funds between accounts, pay bills and prepaid top-up. Mobile banking is a new strategy for the bank to enhance their latest technology in a new dynamic marketing environment.The low penetration of mobile banking in Malaysia, especially in terms of adoption patterns is becoming the research interest, especially when compared to the total number of cellular telephone subscriptions. The penetration rate of mobile banking in Malaysia is still in the minority.One of the issues identified by a few researchers is the perception of trust. This article will discuss along the trust issue and its constituents and then after the intention to use of mobile banking services. The bank should enhance their strategy to improve and develop new strategy in order to gain more utilization and adoption on intention to use. This article attempts to discuss on the element of trust to benefit the service provider in Malaysia.